Unraveling Legal Complexities: Muslim and non-Muslim Estate Administration Process in Malaysia and Brunei - Drs Nasrul, Muhammad Amrullah; A Alihan, Siti Azizah; Hamid, Aimi Atiqah Abdul; Sultan, Benny (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
Estate administration involves managing and distributing a deceased individual’s assets to beneficiaries, as well as managing the liabilities. This process comprises legal, financial, and administrative tasks that ensure assets are transferred based on the deceased's wishes and in accordance with the law. In Southeast Asia countries such as Indonesia, Malaysia and Brunei where Muslims represents the majority of population, the Islamic law plays an integral part in the inheritance management as the process to be in line with the Islamic teachings and principle. The role of the syariah authority namely the syariah courts is prevalent and therefore, abidance to the rule under the syariah legal system in these countries is a must to ensure smoothness and legal compliance. In this with statement, the paper explores inheritance management in Malaysia and Brunei through a comparative legal study, highlighting the distinct frameworks under the common law, Islamic law and customary practices. The study employs a comparative legal research methodology, utilising library-based research by drawing the primary and secondary sources, including statutory provisions, case law, academic literature, and official reports, to examine the legal frameworks, key issues, and recent developments in both jurisdictions. Findings reveal that the highlighted occurring issues require a careful and systematic approach to resolving them to avoid unwanted delay, which prevents the completion of the inheritance management and denies the entitlement of the beneficiaries.